THE USE SUMMARY TECHNIQUES IN EVALUATING THE STUDENTS’ READING ACHIEVEMENT: A CASE STUDY AT THE SECOND YEAR STUDENTS OF MA DARUL AMININ AIK MUAL IN ACADEMIC YEAR 2023/2024 - Novi Hartini; Multazam Multazam (JURNAL ASIMILASI PENDIDIKAN, 2024)
This study is aimed to know are there are positive effects of using sumary in post activity to evaluate the students’ reading achievement at second year students of MA Darul Aminin Aik Mual in academic year 2023/2024. The sample i this study was 66 students, in which 33 students from class XI IPA and XI IPS. The data were collected for more than one month. The method use this study was quantitative effects of using summary in post activity. The writers use multiple choice tests. Base on the study the experimental group is more successful than the student of control group, the deviation of the two mean score (3,12 : 2.6) is also significant as shown the value at t-test 3,058 from the result it can be concluded that the use of summary in post activity have positive effect to evaluate the students reading achievement.